The Internal Ribosome Entry Site-Mediated Translation of Antiapoptotic Protein XIAP Is Modulated by the Heterogeneous Nuclear Ribonucleoproteins C1 and C2 - Holčík, Martin (American Society for Microbiology, 2003)
The X-chromosome-linked inhibitor of apoptosis, XIAP, is the most powerful and ubiquitous intrinsic inhibitor of apoptosis. We have shown previously that the translation of XIAP is controlled by a potent internal ribosome entry site (IRES) element. IRES-mediated translation of XIAP is increased in response to cellular stress, suggesting the critical role for IRES translation during cellular stress. Here, we demonstrate that heterogeneous nuclear ribonucleoproteins C1 and C2 (hnRNPC1 and -C2) are part of the RNP complex that forms on XIAP IRES. Furthermore, the cellular levels of hnRNPC1 and -C2 parallel the activity of XIAP IRES and the overexpression of hnRNPC1 and -C2 specifically enhanced translation of XIAP IRES, suggesting that hnRNPC1 and -C2 may modulate XIAP expression. Given the central role of XIAP in the regulation of apoptosis these results are important for our understanding of the control of apoptosis.